Design and synthesis of liquid crystalline phthalocyanines: combinations of substituents that promote the discotic nematic mesophase. Issue 39 (30th September 2015) - Garland, Andrew D.; Chambrier, Isabelle; Cammidge, Andrew N.; Cook, Michael J.
Abstract: A homologous series of fourteen metal-free 1, 4, 8, 11, 15, 18-hexakis(alkyl)-22-methyl-25-hydroxyalkylphthalocyanine derivatives has been investigated to interrogate the interplay of the roles of the six alkyl chains and the length of the hydroxyalkyl chain in promoting thermotropic nematic liquid crystalline behaviour. All but two of the compounds form mesophases. Eight of the remaining compounds exhibit only columnar mesophases, which is common among liquid crystalline phthalocyanines. However, four examples form the rare discotic nematic mesophase. A general structural feature is deduced in that this rare phase is favoured when the number of linking atoms in the hydroxyalkyl chain exceeds twice the number of carbon atoms in any one of the six common alkyl chains, disrupting the columnar packing arrangement. In addition, zinc and copper metallated examples of one of the metal-free discotic nematic compounds were prepared, of which the zinc metallated compound formed a nematic phase whereas the copper containing analogue favoured columnar mesophase formation. Graphical abstract: